Personalizing the treatment of pediatric medulloblastoma: Polo-like kinase 1 as a molecular target in high-risk children - Triscott, Joanna; Lee, Cathy; Foster, Colleen; Manoranjan, Branavan; Pambid, Mary Rose; Berns, Rachel; Fotovati, Abbas; Venugopal, Chitra; O'Halloran, Katrina; Narendran, Aru; Hawkins, Cynthia; Ramaswamy, Vijay; et al. (Cancer research, 2013)
Medulloblastoma is the most common malignant brain tumor in children. This disease is heterogeneous and is composed of four subtypes of medulloblastoma [WNT, Sonic Hedgehog (SHH), Group 3, and Group 4]. An immediate goal is to identify novel molecular targets for the most aggressive forms of medulloblastoma. Polo-like kinase 1 (PLK1) is an oncogenic kinase that controls cell cycle and proliferation, making it a strong candidate for medulloblastoma treatment. In this study, pediatric medulloblastomas were subtyped in two patient cohorts (discovery cohort, n = 63 patients; validation cohort, n = 57 patients) using NanoString nCounter analysis and PLK1 mRNA was assessed. We determined that the SHH and Group 3 subtypes were independently associated with poor outcomes in children as was PLK1 using Cox regression analyses. Furthermore, we screened a library of 129 compounds in clinical trials using a model of pediatric medulloblastoma and determined that PLK1 inhibitors were the most promising class of agents against the growth of medulloblastoma. In patient-derived primary medulloblastoma isolates, the PLK1 small-molecule inhibitor BI2536 suppressed the self-renewal of cells with high PLK1 but not low PLK1 expression. PLK1 inhibition prevented medulloblastoma cell proliferation, self-renewal, cell-cycle progression, and induced apoptosis. In contrast, the growth of normal neural stem cells was unaffected by BI2536. Finally, BI2536 extended survival in medulloblastoma-bearing mice with efficacy comparable with Headstart, a standard-of-care chemotherapy regimen. We conclude that patients with medulloblastoma expressing high levels of PLK1 are at elevated risk. These preclinical studies pave the way for improving the treatment of medulloblastoma through PLK1 inhibition.
Gesehen am 14.02.2022